2018
DOI: 10.1111/soc4.12622
|View full text |Cite
|
Sign up to set email alerts
|

Selling slumber: American neoliberalism and the medicalization of sleeplessness

Abstract: Sleeplessness is an ancient and cross‐cultural phenomenon that is socially structured and restructured against a backdrop of ideology and inequality. In an effort to make sense of sleeplessness, some scholars have invoked the medicalization framework, which highlights consumerism, managed care, biotechnology, and physicians as key “engines” that foster the transformation of this formerly “normal” condition to one that people view as a medical problem. However, this burgeoning literature has not answered the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 71 publications
0
16
0
1
Order By: Relevance
“…Scholars have identified a number of strategies individuals use to regulate their sleep and manage sleep‐related problems, including “personalized strategies” such as having a warm drink or taking a shower before bed (Hislop & Arber, 2003b), medicalization via diagnoses or the use of various pharmaceuticals (Coveney, Williams, & Gabe, 2018; Moloney, 2017), and customization strategies such as workplace napping or the use of wakefulness‐promoting drugs (Williams, Coveney, & Gabe, 2013). Further, the growing expectation that individuals must successfully manage sleep‐related issues has facilitated the commodification of sleep, resulting in an expanding number of consumer products and services available for the enhancement of sleep (Barbee, Moloney, & Konrad, 2018; Mooallem, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have identified a number of strategies individuals use to regulate their sleep and manage sleep‐related problems, including “personalized strategies” such as having a warm drink or taking a shower before bed (Hislop & Arber, 2003b), medicalization via diagnoses or the use of various pharmaceuticals (Coveney, Williams, & Gabe, 2018; Moloney, 2017), and customization strategies such as workplace napping or the use of wakefulness‐promoting drugs (Williams, Coveney, & Gabe, 2013). Further, the growing expectation that individuals must successfully manage sleep‐related issues has facilitated the commodification of sleep, resulting in an expanding number of consumer products and services available for the enhancement of sleep (Barbee, Moloney, & Konrad, 2018; Mooallem, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in DTCA may also impact prescription rates. As recently described by Barbee and colleagues (Barbee et al, 2018), DTCA for NBSH has fallen off steeply in recent years 3. For context, makers of Ambien and Ambien CR, the most popular of the newer-generation sedative-hypnotics spent $147 million on DTCA in 2008, a time of economic recessesion (Weinstein, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…Quantitative and qualitative research has identified multiple social and behavioral factors (e.g., career uncertainty, near-constant use of light-producing technology, worry over children or aging parents) that are closely linked to sleep loss and request for sleep aids (Moloney, 2017; Seidel, Yorgason, Polenick, Zarit, & Fingerman, 2017; Thomee, Harenstam, & Hagberg, 2011). Additional factors, particularly relevant to the United States and its aging, Baby Boom generation, that fuel the multi-billion dollar “Sleep-Industrial Complex” include: enhancement culture (self-transformation through techno-science), commodification of health (creation of niche health-services and products), and a “productivity imperative” (maximizing productivity in a 24/7 work culture) (Barbee et al, 2018). Future research could specifically investigate the extent to which these and other factors contribute to changing attitudes and practices related to sedative-hypnotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient sleep is critical for health and well-being in older adults (Grandner, 2019), yet 20% to 30% of this population meet the diagnostic criteria for chronic insomnia (Neikrug & Ancoli-Israel, 2010). Increased awareness of sleep's importance to health has coincided with the development, promotion, and increased prescription of sleep medications (Barbee et al, 2018;Bertisch et al, 2014;Grandner, 2019;Mooallem, 2007). Between 1993 and 2007, rates of sleep medication prescriptions increased 30-fold in the United States (U.S.) (Moloney et al, 2011).…”
Section: Introductionmentioning
confidence: 99%